Greek heritage in Romanian and Aromanian languages - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2012)
This article analyses the Greek influence upon two major Balkan Romance languages, Romanian and Aromanian (the most affected, as it seems, by this influence, historically, like Romanian, and also contemporarily, like Aromanian). In Romanian, for the period of the strongest Greek impact, the Greek lexicon is estimated to be over 10%, but in the contemporary language, the words of Greek origin represent only 2%. In Aromanian, due to its constant contact with Modern Greek (especially in Greece), Greek borrowings are extremely common, expressing not only abstract and specialized terminology, but also many notions of everyday life. Besides the Greek elements in Romanian and Aromanian vocabulary, we notice a number of phonetic, phonological, morphological and syntactic features of Greek origin, either obvious or potential. They appear especially in Aromanian, which borrowed some Greek phonemes and morphemes (both inflectional and derivational) and also adopted, more constantly than Romanian, some syntactic constructions, possibly of Greek origin.